A Case of Tubular Apocrine Adenoma with Syringocystadenoma Papilliferum that Developed in a Nevus Sebaceus - Kim, Mi Sun; Lee, June Hyunkyung; Lee, Won-Mi; Son, Sook-Ja (Annals of dermatology, 2010)
Tubular apocrine adenoma (TAA) is a very rare sweat gland tumor. TAA and syringocystadenoma papilliferum (SCAP) rarely develop together in a nevus sebaceus (NS). Herein, we report on a 40-year-old Korean woman with TAA associated with SCAP that developed in a NS located on the scalp.